MARKETING STRATEGY IN PROJECT SUSTAINABILITY MANAGEMENT EFFORTS IN EXTRACTIVE INDUSTRIES: BUILDING A RECIPROCITY FRAMEWORK FOR COMMUNITY ENGAGEMENT - Zaenal Aripin; Sri Rochani Mulyani; Adang Haryaman (KRIEZ ACADEMY : Journal of development and community service, 2023)
Extractive industries often face significant sustainability challenges, particularly regarding the social and environmental impacts of their activities. In this context, marketing strategy has a key role in shaping the company's image, responding to community expectations, and building project sustainability. Building a reciprocity framework for community engagement is becoming an increasingly recognized approach to achieving this goal. This research aims to explore and analyze the implementation of marketing strategies in project sustainability management efforts in the extractive industry, with a focus on building a reciprocity framework to increase community involvement. The main objective is to identify the key factors that influence the success of sustainable marketing strategies and their impact on community engagement. This research uses a descriptive qualitative approach with a multiple case study of companies in the extractive industry that have adopted sustainable marketing strategies and a reciprocity framework. Data was collected through in-depth interviews with key stakeholders, analysis of related documents, and direct observation of marketing strategy implementation. The research results show that implementing marketing strategies in project sustainability management in extractive industries by building a reciprocity framework can create a positive impact on community involvement. Factors such as transparency, community participation and local empowerment have a critical role in shaping project sustainability and improving relations between companies and local communities.